Impaired TFEB-mediated lysosomal biogenesis promotes the development of pancreatitis in mice and is associated with human pancreatitis. Issue 11 (2nd November 2019) - Wang, Shaogui; Ni, Hong-Min; Chao, Xiaojuan; Wang, Hua; Bridges, Brian; Kumer, Sean; Schmitt, Timothy; Mareninova, Olga; Gukovskaya, Anna; De Lisle, Robert C.; Ballabio, Andrea; Pacher, Pal; et al.
ABSTRACT: Impaired macroautophagy/autophagy has been implicated in experimental and human pancreatitis. However, the transcriptional control governing the autophagy-lysosomal process in pancreatitis is largely unknown. We investigated the role and mechanisms of TFEB (transcription factor EB), a master regulator of lysosomal biogenesis, in the pathogenesis of experimental pancreatitis. We analyzed autophagic flux, TFEB nuclear translocation, lysosomal biogenesis, inflammation and fibrosis in GFP-LC3 transgenic mice, acinar cell-specific tfeb knockout (KO) and tfeb and tfe3 double-knockout (DKO) mice as well as human pancreatitis samples. We found that cerulein activated MTOR (mechanistic target of rapamycin kinase) and increased the levels of phosphorylated TFEB as well as pancreatic proteasome activities that led to rapid TFEB degradation. As a result, cerulein decreased the number of lysosomes resulting in insufficient autophagy in mouse pancreas. Pharmacological inhibition of MTOR or proteasome partially rescued cerulein-induced TFEB degradation and pancreatic damage. Furthermore, genetic deletion of tfeb specifically in mouse pancreatic acinar cells increased pancreatic edema, necrotic cell death, infiltration of inflammatory cells and fibrosis in pancreas after cerulein treatment. tfeb and tfe3 DKO mice also developed spontaneous pancreatitis with increased pancreatic trypsin activities, edema and infiltration of inflammatory cells. Finally, decreased TFEB nuclear staining was associated with human pancreatitis. In conclusion, our results indicate a critical role of impaired TFEB-mediated lysosomal biogenesis in promoting the pathogenesis of pancreatitis. Abbreviations: AC: acinar cell; AMY: amylase; ATP6V1A: ATPase, H+ transporting, lysosomal V1 subunit A; ATP6V1B2: ATPase, H+ transporting, lysosomal V1 subunit B2; ATP6V1D: ATPase, H+ transporting, lysosomal V1 subunit D; ATP6V1H: ATPase, H+ transporting, lysosomal V1 subunit H; AV: autophagic vacuole; CDE: choline-deficient, ethionine-supplemented; CLEAR: coordinated lysosomal expression and regulation; CQ: chloroquine; EIF4EBP1: eukaryotic translation initiation factor 4E binding protein 1; EM: electron microscopy; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; H & E: hematoxylin and eosin; KO: knockout; LAMP1: lysosomal-associated membrane protein 1; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MAPK1/ERK2: mitogen-activated protein kinase 1; MTORC1: mechanistic target of rapamycin kinase complex 1; ND: normal donor; NEU: neutrophil; PPARGC1A/PGC1α: peroxisome proliferator-activated receptor, gamma, coactivator 1 alpha; RIPA: radio-immunoprecipitation; RPS6: ribosomal protein S6; SQSTM1/p62: sequestosome 1; TFEB: transcription factor EB; TM: tamoxifen; WT: wild-type; ZG: zymogen granule